Simultaneous adoption of integrated soil fertility management technologies in the Chinyanja Triangle, Southern Africa - Mponela, Powell; Kassie, Girma T.; Tamene, Lulseged D. (Wiley, 2018)
Empirical scientific evidence indicates that there is still room for increasing food production by improving land productivity. This study aimed at identifying the key determinants that govern farmers’ decisions to adopt multiple components of integrated soil fertility management (ISFM) in a maize mixed cropping system of the Chinyanja Triangle, Southern Africa. Revealed preferences of ISFM components were collected from 320 randomly selected households and multivariate probit (MVP) model was used to analyse the simultaneous effects on adoption based on biophysical plot and household‐level socioeconomic attributes. The results show that farmers’ choices of a set of ISFM components are determined by a mix of factors that address the trade‐offs and synergies among them. Non‐farm income, moderate land quality perception, and education influence simultaneous technology adoption, while gender and crop loss increase the likelihood of farmers’ decisions to adopt independent options. Having other sources of income supports co‐adoption of inorganic fertilizer, residue incorporation, and crop rotation. Input/output market access, access to information, financial sources, and climate variability also play pivotal role in technology adoption. These results indicate that resource availability, learning costs, finances, and risk aversion need to be considered when designing and promoting ISFM technologies as a package.